2018
DOI: 10.4317/jced.54548
|View full text |Cite
|
Sign up to set email alerts
|

Biological and physico-chemical properties of new root canal sealers

Abstract: BackgroundThe purpose of the present study was to compare the biological and the physico-chemical properties of bioceramic-based root canal sealers, calcium hydroxide-based, MTA-based and epoxy resin-based root canal sealers.Material and MethodsTwo bioceramic-based sealers, one calcium hydroxide-based sealer, one MTA-based sealer and two epoxy resin-based sealers were tested.ResultsEasySeal and MTA Fillapex showed severe citotoxic activity, AH Plus and SealapexTM moderate cytotoxicity, BioRoot™ RCS and TotalFi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
92
3
16

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(121 citation statements)
references
References 23 publications
10
92
3
16
Order By: Relevance
“…TFB and BCR showed similar results in terms of cell viability as compared with a control group. In line with this work, previous reports have described similar results, also using the MTT test with TotalFill BC sealer, which has an almost identical composition, except it changes consistency [25,26]. Benetti et al [27] also reported that BCR is a biocompatible material that induces mineralization in vivo.…”
Section: Discussionsupporting
confidence: 85%
“…TFB and BCR showed similar results in terms of cell viability as compared with a control group. In line with this work, previous reports have described similar results, also using the MTT test with TotalFill BC sealer, which has an almost identical composition, except it changes consistency [25,26]. Benetti et al [27] also reported that BCR is a biocompatible material that induces mineralization in vivo.…”
Section: Discussionsupporting
confidence: 85%
“…, Colombo et al . ). Recently, the new calcium silicate‐based Sealer Plus BC (MK Life, Porto Alegre, RS, Brazil) and Bio‐C Sealer (Angelus, Londrina, PR, Brazil) were developed and introduced.…”
Section: Introductionmentioning
confidence: 97%
“…Premixed, ready-to-use calcium silicatebased endodontic sealers, such as EndoSequence (Brasseler, Savannah, GA, USA) and TotalFill BC Sealer (FKG Dentaire, La Chaux-de-Fonds, Switzerland), have been studied (Zamparini et al 2019). TotalFill BC has adequate physicochemical properties, but appears to be soluble (Poggio et al 2017, Tanomaru-Filho et al 2017, Colombo et al 2018. Recently, the new calcium silicate-based Sealer Plus BC (MK Life, Porto Alegre, RS, Brazil) and Bio-C Sealer (Angelus, Londrina, PR, Brazil) were developed and introduced.…”
Section: Introductionmentioning
confidence: 99%
“…Potencial de hidrogeniones (pH): Los productos de tipo MTA tienen un pH inicial de 10,2, que se eleva a 12,5 tres horas después de la mezcla, manteniéndose constante (Torabinejad et al, 1995). Aunque el MTA Fillapex de acuerdo a las evaluaciones observadas por Colombo et al (2018) el pH a las 3 horas posteriores a su aplicación e incubación exhibe un pH inicial de 7,68 que fue seguido por un pH alcalino débil pasadas las 24 horas a 8,02.…”
Section: Propiedadesunclassified
“…Biocompatibilidad: BioRoot TM RCS es altamente biocompatible, no altera la arquitectura celular, cuya integridad es necesaria para las funciones basales celulares (Loison-Robert et al, 2018). De acuerdo a una investigación realizada recientemente no presenta un efecto citotóxico (Colombo et al, 2018; en contacto directo o indirecto y la genotoxicidad resulto negativa. Tampoco las células expresaban IL-1β o metaloproteinasa de matriz 9 (MMP-9), y la metaloproteinasa 2 de matriz (MMP-2) las cuales están asociadas con respuestas inflamatorias (Loison-Robert et al, 2018).…”
Section: Propiedadesunclassified